Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1093/jnci/djp534
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Papillomavirus (HPV)-6/11/16/18 Vaccine on All HPV-Associated Genital Diseases in Young Women

Abstract: High-coverage HPV vaccination programs among adolescents and young women may result in a rapid reduction of genital warts, cervical cytological abnormalities, and diagnostic and therapeutic procedures. In the longer term, substantial reductions in the rates of cervical, vulvar, and vaginal cancers may follow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
293
0
17

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(329 citation statements)
references
References 34 publications
15
293
0
17
Order By: Relevance
“…However, 2nd and 3rd doses could have been given in the calendar year they turned 14 or in the calendar year they turned 15 years old respectively, depending on the date of the first dose and scheduled clinics. 2 Rate of completed HPV vaccine series for birth cohort in province reported from the provincial vaccine registry. arm and placebo arm for their main outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 2nd and 3rd doses could have been given in the calendar year they turned 14 or in the calendar year they turned 15 years old respectively, depending on the date of the first dose and scheduled clinics. 2 Rate of completed HPV vaccine series for birth cohort in province reported from the provincial vaccine registry. arm and placebo arm for their main outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials have shown that both the quadrivalent and bivalent HPV vaccines are highly efficacious in preventing HPV infection, cervical dysplasia, anal dysplasia and in the case of the quadrivalent vaccine, genital warts. [1][2][3][4][5] As part of the introduction of HPV vaccine globally, jurisdictions that started public programs were encouraged to embark on comprehensive monitoring programs to determine HPV vaccine safety, uptake, acceptability and impact of the program on HPV prevalence, cervical dysplasia and ultimately, cervical cancer. 6 Data from Australia, the United States and the United Kingdom have shown that the vaccine is effective, with population level reductions in rates of genital warts, HPV and cervical cancer lesions.…”
mentioning
confidence: 99%
“…31 Data from two recently conducted randomised trials of HPV vaccines in young women demonstrated a 95% reduction in a combined endpoint of high grade vaginal or vulval intraepithelial neoplasia realted to HPV-16 and -18 in women who were initially unexposed to HPV. 35 …”
Section: Vaginal Cancermentioning
confidence: 99%
“…34,35 Therefore, timely vaccination can prevent a fair part of the HPV disease burden. After the onset of vaccination referrals to colposcopy and CIN cases will first be prevented.…”
Section: Discussionmentioning
confidence: 99%